Velocity-based robust fault tolerant automatic steering control of autonomous ground vehicles via adaptive event triggered network communication. (September 2020) - Li, Wenfeng; Xie, Zhengchao; Zhao, Jing; Wong, Pak Kin
Graphical abstract: Highlights: A polytope is proposed for uncertain dynamic features and time-varying velocity. A more general network-induced delay is considered via a novel Lyapunov function. The actuator fault is considered to strengthen the robustness of the controller. An adaptive event triggered scheme is proposed for the robust fault tolerant control. Abstract: This paper proposes a velocity-based robust fault tolerant automatic steering control approach for autonomous ground vehicles via an adaptive event triggered network communication mechanism. Firstly, as the vehicle longitudinal velocity is not fixed but time-varying, a polytope with finite vertices is adopted to construct a linear parameter varying vehicle system model. Secondly, since network-induced delay and actuator fault inevitably occur in the control system, a novel Lyapunov function is formulated to guarantee the asymptotical stability of the closed-loop system. Moreover, an advanced event triggered communication scheme is proposed for the co-design of robust automatic steering controller, which is quite effective to reduce network communication burden and enhance resource utilization of the shared band-limited in-vehicle communication network. Finally, numerical simulations on two cases are carried out to evaluate and verify the effectiveness and robustness of the proposed controller. Compared with existing studies, the proposed controller contributes greatly to the economization of communication resource and improvement of path following performance and lateral stability.